(untitled) (Scientific journal of the Fergana State University, 2024)
Legal education is a purposeful, constant influence on a person with the aim of developing a legal culture and active legal behavior. The article shows the pedagogical factors of organizing the legal education of students on the basis of independent educational activities, the goals and objectives of legal education, the main elements of the mechanism for organizing the legal education of students on the basis of independent educational activities.